(untitled) (Indian Journal of Animal Production and Management, 2014)
Two hundred ten day old commercial broiler chicks divided into seven groups (T0 - control, T1, T2, T3, T4, T5 and T6) of 30 chicks were allotted to four iso-nitrogenous dietary treatments, viz. D0, D1, D2 and D3, containing 0 (control), 10, 15 and 20 per cent of DORB for 6 weeks followed by a metabolic trial. T1, T2 and T3 groups were offered experimental diets –D1, D2 and D3 from 0-42 days and T4, T5 and T6 groups were offered from 22-42 days respectively. The average body weight gain, feed consumption and feed conversion ratios did not differ significantly (P>0.05) among the groups; however, the digestibility of CF was significantly (P<0.01) higher at 10 per cent level and the retention of phosphorus was significantly (P>0.05) lower at 20 per cent level of DORB inclusion irrespective of the stages of feeding.